AUTONOMOUS SOLUTIONS FOR DESIGN AND IMPLEMENTATION OF MODULAR STRUCTURES (Balkan Journal of Applied Mathematics and Informatics, 2024)
Our objective with this paper is to analyze and explore emerging autonomous solutions for designing and implementing modular structures. Modular structures have been in use since the 1950s, so the concept is not new to us. Historically, the popularity of modular structures peaked following catastrophic natural disasters or wars, in areas that required rapid rebuilding. However, modular construction somewhat fell out of favor afterward. Nowadays, its popularity is resurging, becoming a notable trend once again. The robots employed in modular construction offer distinct advantages over those used in traditional construction, with streamlined tasks and enhanced efficiency. In this paper, we plan to analyze drones, loaders, cranes, and worker bots. These robots will serve various roles, including observation, construction, organization, and excavation. Furthermore, we aim to integrate these robots with cutting-edge technologies such as artificial intelligence, augmented and virtual reality, the internet of things, cloud services, and building information modeling - BIM.